Prisoners' View of Boards of Visitors. A Question of Credibility - Martin, Carol (The British journal of criminology, 1994)
Explores the awareness of prisoners in Great Britain of the role and duties of the Boards of Visitors (BOV). Creation of the BOV in 1992 to deal with serious offenses against prison discipline; BOV as ineffective and irrelevant to prison management